Health workers and family support with the adequacy of breast milk in perinatal room - Munica Rita Hernayanti; Yuliasti Eka Purnamaningrum; Maranata Maratana (Jurnal Kesehatan Ibu dan Anak, 2020)
LWB is the most common cause of infant infant death. Breastfeeding is one treatments for LBW. This study aims to determine the support of health workers and families to the adequacy of breastfeeding in mothers who have LBW. This study was a quantitative analytic study with a cross-sectional design. The sampling technique used is an accidental sampling with total 97 subjects. Results of this study stated significant relationship between the support of health workers and the adequacy of breast milk (x2=4.581; p= 0.032; OR= 2.874) and significant relationship between the support of family and the adequacy of breast milk ASI (x2=4.619; p= 0.042; OR= 2.810). Based on the results can be used to formulated SOP for mentoring health workers and families for mothers who have LBW in the perinatal room of the DIY regional hospital and can also formulate leaflets as guidance mentoring to mothers.